Caffeine in Pain Perception and Management - Piekarska, Ewa; Pawlicki, Mateusz; Łopuszyńska, Anna; Kozioł, Magdalena; Krasa, Aleksandra; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2021)
Introduction: Caffeine is considered to be one of the most frequently used pharmacologically active substances in the world. Caffeine is a psychoactive and central nervous system stimuli that has the ability to increase energy, decrease fatigue, promote alertness and wakefulness. Potential role of caffeine's nociceptive properties shows that it may play a relevant role in pain modulation. Although caffeine at dietary levels is not a sufficient analgesic in its own, it has been included in many over-the-counter and prescription drugs. This review addresses caffeine's analgesic properties in pain management. Results: Caffeine shows relevant role in pain modulation through blocking adenosine receptors which are involved in nociception. Studies show that habitual dietary caffeine consumption results in decreased pain sensitivity.As an adjuvant to commonly used analgesics, caffeine provides an important increase in pain relief in various types of pain such as postoperative dental pain, headaches, or fibromyalgia. Conclusions: In conclusion, caffeine is associated with decreased pain sensitivity. Addition of caffeine to analgesics has resulted in their enhanced analgesic efficacy in pain treatment.